Cost-Effectiveness of Repository Corticotropin Injection versus Standard of Care for the Treatment of Active Rheumatoid Arthritis - Bindra J; Chopra I; Niewoehner J; Panaccio M; Wan GJ (Dove Medical Press, 2021)
Jas Bindra,1 Ishveen Chopra,2 John Niewoehner,3 Mary Panaccio,3 George J Wan3 1Falcon Research Group, North Potomac, MD, USA; 2Manticore Consultancy, Bethesda, MD, USA; 3Mallinckrodt Pharmaceuticals, Hampton, NJ, USACorrespondence: George J WanMallinckrodt Pharmaceuticals, 53 Frontage Road, Hampton, NJ, 08827, USAEmail george.wan@mnk.comIntroduction: Patients with active rheumatoid arthritis (RA) often have inadequately controlled symptoms and are unable to achieve remission or low disease activity despite aggressive treatment. This results in irreversible joint damage, adversely affecting patients’ physical and social functioning. The objective was to estimate the cost-effectiveness of repository corticotropin injection (RCI) versus standard of care (SoC) in patients with active RA from the United States (US) payer and societal perspectives over two to three years.Methods: An individual-level microsimulation was developed to generate individual trajectories for patients with RA, using data from a published Phase 4 trial of RCI. These trajectories report a patient’s disease pathway and associated cost and quality-of-life outcomes. The incremental cost-effectiveness ratio (ICER) of RCI versus SoC was assessed using the literature-derived direct medical and indirect costs, and quality-adjusted life-years (QALY) derived from a Phase 4 trial of RCI. The uncertainty in base case estimates of the parameters was evaluated in the sensitivity analysis.Results: Over two years, RCI has an incremental QALY gain of 1.591 and incremental cost of $183,965 and $117,443 from payer and societal perspective, respectively, resulting in an ICER of $115,629/QALY and $73,817/QALY compared to SoC. Over three years, RCI has an incremental QALY gain of 2.336 and incremental cost of $202,315 and $104,506 from payer and societal perspective, respectively, resulting in an ICER of $86,607/QALY and $44,737/QALY compared to SoC. Results from the probabilistic sensitivity analysis are consistent with those of the base case model.Conclusion: RCI is a cost-effective strategy for patients with persistently active RA who are previously treated with disease-modifying anti-rheumatic drugs and corticosteroids compared to SoC over two to three years from the payer and societal perspectives at a US willingness-to-pay threshold of $150,000/QALY. Further, the economic benefit of RCI is realized with improvement in a patient’s clinical and health outcomes.Keywords: Acthar® Gel, cost-effectiveness analysis, low-disease activity, repository corticotropin injection, rheumatoid arthritis